English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
0

If:

f(x) = 3x-4 and g(n) = (n+4)/3

g(t+5) = -7
find t

How?
(sorry for repost)

2007-03-24 18:27:56 · 7 answers · asked by John D 2 in Science & Mathematics Mathematics

7 answers

g(t+5)=[(t+5)+4]/3=-7
Therefore, t+9=-21 and t=-30.

2007-03-24 18:34:39 · answer #1 · answered by bruinfan 7 · 0 0

I don't see any use for the function f(x), so I'm going to guess that we're trying to answer part of a longer problem.

If g(n) = (n+4)/3, then substitute t+5 for n:

g(t+5) = [(t+5) +4]/3 = -7;
t+5+4 = -7*3
t+9= -21
t = -30

Check: g(t+5) = g(-25) = (-25+4)/3 = -21/3 = -7.

Good luck, work hard, and stay away from drugs.

2007-03-25 01:38:31 · answer #2 · answered by MikeyZ 3 · 0 0

g(t+5) = ((t+5) + 4)/3 = (t+9)/3 from the definition of g(n)
But g(t+5) = -7
So (t+9)/3 = -7. Therefore t+9 = -21 so t = -30.

The fact that f(x) = 3x - 4 is irrelevant to finding t.

2007-03-25 01:35:05 · answer #3 · answered by Bazz 4 · 0 0

g(n) = (n+4)/3
thus, g(t+5) = ((t+5)+4)/3 = (t+9)/3=-7
=> t+9 = 3*(-7)=-21
=> t = -21-9 = -30

2007-03-25 01:41:13 · answer #4 · answered by Thor 1 · 0 0

Well, um you don't even need the first f(x) part.
Okay: so:

g(t+5) = ((t+5)+4)/3 = 8
t+9 = 24
t = 15

whoops, sorry. This is wrong because I thought you wrote 7 instead of -7.

2007-03-25 01:33:24 · answer #5 · answered by Bob R. 6 · 0 0

If g(n) = (n + 4)/3, g(t + 5) = ((t + 5) + 4)/3
So, g(t + 5) = (t + 9)/3

If g(t + 5) = -7
(t + 9)/3 = -7
t + 9 = -21
t = -30

2007-03-25 01:35:00 · answer #6 · answered by polymac98 2 · 0 0

plug t+5 into n

g(t+5) = [(t+5)+4]/3 = -7

(t+9)= -21
t = -30

2007-03-25 01:36:49 · answer #7 · answered by HayatoK 2 · 0 0

fedest.com, questions and answers